Tectono-magmatic Interplay and Related Metasomatism in Gabbros of the Chenaillet Ophiolite (Western Alps). (15th February 2020) - Tribuzio, R; Manatschal, G; Renna, M R; Ottolini, L; Zanetti, A
Abstract: The Jurassic Chenaillet ophiolite in the Western Alps consists of a gabbro–mantle association exhumed to the seafloor through detachment faulting and partly covered by basaltic lavas. One of the Chenaillet gabbroic bodies includes mylonites that are transected by a network of felsic veins, thereby testifying to the interplay of ductile shearing and magma emplacement. The deformed gabbros preserve clinopyroxene porphyroclasts of primary magmatic origin, which are typically mantled by amphibole (titanian edenite) and minor secondary clinopyroxene. Titanian edenite and secondary clinopyroxene also occur as fine-grained syn-kinematic phases locally associated with fine-grained plagioclase. The felsic veins are made up of anorthite-poor plagioclase and minor titanian edenite. Geothermometric investigations document that the ductile gabbro deformation and the crystallization of the felsic veins occurred at 765 ± 50 °C and 800 ± 55 °C, respectively. With respect to undeformed counterparts, the deformed gabbros are variably enriched in SiO2 and variably depleted in Mg/(Mg + Fe tot 2 + ) and Ca/(Ca + Na). In addition, the deformed gabbros show relatively high concentrations of incompatible trace elements such as rare earth elements (REE), Y, Zr and Nb. The felsic veins are characterized by low Mg/(Mg + Fe tot 2 + ) and Ca/(Ca + Na), high SiO2 and high concentrations of incompatible trace elements. Relict clinopyroxene porphyroclasts from the deformed gabbros display a rather primitive, mid-ocean ridge-type geochemical signature, which contrasts with the trace element fingerprint of titanian edenite from both the deformed gabbros and the felsic veins. For instance, titanian edenite typically has relatively high REE abundances, with chondrite-normalized REE patterns characterized by a pronounced negative Eu anomaly. A similar trace element signature is shown by secondary clinopyroxene from the deformed gabbros. Amphibole from both the deformed gabbros and the felsic veins displays high F/Cl values. We show that the SiO2 -rich hydrous melts feeding the felsic veins were involved in the high-temperature gabbro deformation and that melt–gabbro reactions led to major and trace element metasomatism of the deforming gabbros.